Suplementação de probióticos em ovos férteis de matrizes de corte - Delavy, Fernanda Moreira (2021)
The poultry industry has undergone several transformations over the last years. Currently, the nutrition in ovo is a procedure that allow providing different types of nutrients to the embryo, supplying the nutritional deficiencies at this stage. Probiotics are relevant microorganisms for the performance of animals, providing satisfactory effects on production. This study aimed to verify the influence of in ovo probiotic on embryonic development and poultry production. In the first stage, it was done a completely randomized design, with 3 treatments (control; comercial Mareck vaccine; and in ovo probiotics with Mareck vaccine). There were used 192 eggs per tretment, totaling 576 eggs. On the day of birth, the percentage of hatchability, the infective ones and the cause of mortality of the embryos that were submitted to the treatments were evaluated, which in turn showed no difference (p>0,05). The values of weight, length, weight without the yolk sac, bowel weight, yolk sac weight, liver weight, heart weight, and stomach weight with the gizzard of the chicks that were vaccinated in ovo showed similar results with the control treatments (p>0,05) what meant that the inoculation procedure did not affect the development of the birds. The variables to determine the quality of the chicks, referring to birth, did not differ between treatments. For the field experiment, the birds remained separated according to the treatment made in the hatchery, that is, the 3 treatments used in the first stage with 8 repetitions (per treatment), totaling 24 groups with 20 birds each. In addition, after the 21 life day, two birds per repetition were euthanized to verify the development of organs. No significant differences were found in the bird weight, the intestine weight, the liver weight, the weight of the heart, and the weight of the stomach plus the gizzard within the 3 treatments. Thus, the inoculation did not affect the development of organs in chickens either. It is concluded that the tested probiotic did not provide negative effects on embryonic development and production of broiler chickens.